Carcinoid Syndrome Complicating a Pancreatic Neuroendocrine Tumor: A Case Report. Issue 10 (November 2017) - Gerson, James N.; Witteles, Ronald M.; Chang, Daniel T.; Beygui, Ramin E.; Iagaru, Andrei H.; Kunz, Pamela L.
Abstract : Abstract: Neuroendocrine tumors (NETs) comprise a heterogeneous group of neoplasms. These tumors can produce a wide variety of hormones that can lead to syndromes of hormone excess, such as carcinoid syndrome. We present the case of a 47-year-old man who presented with right upper quadrant abdominal pain and emesis. He was found to have metastatic pancreatic NET and was treated with systemic chemotherapy. He subsequently developed dyspnea on exertion and was found to have severe right-sided heart disease secondary to elevated levels of serum serotonin. He was successfully treated with surgical tricuspid and pulmonic valve replacement. True carcinoid syndrome with pancreatic NETs is rare, but, as a treatable complication of the disease, is an important entity for which oncologists should be familiar.